2000
DOI: 10.1366/0003702001950508
|View full text |Cite
|
Sign up to set email alerts
|

Flow Analysis-Based Surface-Enhanced Raman Spectroscopy Employing Exchangeable Microbeads as SERS-Active Surfaces

Abstract: This paper reports on a new fully automated approach for highly sensitive and robust surface-enhanced Raman spectroscopic (SERS) detection using flow systems. An aqueous solution of silver nitrate was reduced by the addition of sodium borohydride and the thus formed silver sols adsorbed on Sephadex anion exchanger microbeads (dry bead size: 50–120 μm) present in the reaction mixture. In this way microbeads carrying a SERS-active layer were generated that could be easily pumped in the flow system without facing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Since our methodology provides a simple and versatile tool for broadening the choice of colors for metal NPs, it is expected that it can be more widely used for surface-enhanced Raman scattering (SERS), [7,9] multiplexed optical bar coding, [22] optical-contrast agents, [23] photonic crystals, [24] colorimetric detection, [16] flow cytometry, [25] and cryptography. [26] The basic principle for the color-tuning of micro-and nanospheres described in this report may be easily extended to the fabrication of other types of functional microstructures, such as core/shell-type micro-and nanospheres [27] (metal NPs located in the interiors of polymer spheres, silica spheres, and hydrogel spheres) and film structures (metal NPs dispersed in polymer or silica films).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since our methodology provides a simple and versatile tool for broadening the choice of colors for metal NPs, it is expected that it can be more widely used for surface-enhanced Raman scattering (SERS), [7,9] multiplexed optical bar coding, [22] optical-contrast agents, [23] photonic crystals, [24] colorimetric detection, [16] flow cytometry, [25] and cryptography. [26] The basic principle for the color-tuning of micro-and nanospheres described in this report may be easily extended to the fabrication of other types of functional microstructures, such as core/shell-type micro-and nanospheres [27] (metal NPs located in the interiors of polymer spheres, silica spheres, and hydrogel spheres) and film structures (metal NPs dispersed in polymer or silica films).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, they have been widely explored as substrates for use in Raman scattering, [7] chemical and biological sensing, [8] and colloidal metal sensors. [9] Most of these applications require that the SPR band should be tuned over a broad range. Recently, several approaches have been developed to tune the SPR peak from visible to near-IR (NIR) wavelengths by synthesizing metal NPs that have various sizes and geometries (nanoshells, [10] nanocubes, [11] nanorods, [12] nanoprisms, [13] etc.).…”
Section: Introductionmentioning
confidence: 99%
“…A particular spectroscopic detection developed for flow SIA determinations with beads suspension is surface-enhanced Raman spectroscopy (SERS) [23,24]. This scattering method requires a stable solid surface, stabilized, for example, by appropriate electric polarization or use of noble metals such as gold or silver colloids as substrates.…”
Section: Detection Methods Employed In Flow Systems With Particle Susmentioning
confidence: 99%
“…For the determination of radionuclides 90 Sr, 99 Tc, and 241 Am specially developed selective ionexchange resins have been used [22]. An anion-exchange resin with adsorbed silver sols was applied as the active surface with nicotinic acid as a model analyte in a flow analysis-based surface-enhanced Raman spectroscopy (SERS) study [23]. In a sequential injection analysis (SIA), a flow system with the same detection for the determination of 9-aminoacridine, cation-exchange beads were used with an active layer surface formed on the bead surface [24].…”
Section: Solid Microparticles Used In Suspensions In Flow Analysismentioning
confidence: 99%
“…The particles resemble the SERRS-active microbeads of Lendl and co-workers. [11,12] and we have obtained strong SERRS spectra from our beads in our standard Raman instrument. However, we also observed that the partial silver coating allowed many of these particles to be trapped in three dimensions within a conventional optical-tweezers setup without recourse to annular or scanning beams.…”
mentioning
confidence: 99%